Bone Formation with Two Types of Grafting Materials: A Histologic and Histomorphometric Study - Rokn, Amir Reza (Bentham Open, 2011)
BACKGROUND: Although autogenous bone grafts are considered the gold standard for bone regeneration, they have certain limitations, including patient morbidity at the harvest site. Synthetic bone substitutes have been developed to overcome some of these limitations. The present study aimed to compare the osteogenic properties of Straumann Bone Ceramic (SBC), which is a biphasic calcium phosphate, with Bio-Oss, an inorganic bovine bone material, in an animal model. METHODS: Thirteen rabbits were included in this study. In each rabbit, four 6.5-mm-diameter identical defects were prepared on the calvarium. One site was filled with Bio-Oss, the second site was treated with small-particle SBC, the third site was treated with large-particle SBC, and the fourth site was left as an untreated control. After 4 and 8 weeks, the animals were sacrificed, and histologic and histomorphometric examinations were performed. The data were analyzed using Friedman and multiple-comparison Mann-Whitney U tests. RESULTS: There were no statistically significant differences in the amount of bone fill between the four groups. L-SBC showed more inflammation and foreign-body reactions than the other bone substitutes. CONCLUSION: No statistically significant differences were found between groups. Further studies on this issue seem necessary.